Konflik Antartokoh dalam Novel Aishū Shinderera Mō Hitori No Shinderera Karya Akiyoshi Rikako - Gony, Alda Purnama; Anwar, Fithyani (NAWA: Journal of Japanese Studies, 2024)
This research aims to analyze the conflicts between characters in the novel Aishū Shinderera mō Hitori no Shinderera by Akiyoshi Rikako by delineating the forms of conflicts between characters and the underlying factors contributing to these conflicts. A qualitative descriptive method is employed in this study with a structural approach, focusing on the analysis of intrinsic elements that shape literary works. Data collection involves a literature review of literature and the utilization of both Japanese and Indonesian-translated versions of the novel. Overall, the research successfully gathers data on 45 interpersonal conflicts and 41 contributing factors. The data generated from this research encompass the forms of interpersonal conflicts and the factors underlying these conflicts within the novel.